Demos before Democracy: Ideas of nation and society in Adam Smith. (November 2015) - Hearn, Jonathan
What did Adam Smith understand by the term 'nation' in The Wealth of Nations ? This article uses this relatively simple question as a way of exploring the roots of current debates about the concept of the nation, prevalent in the study of nationalism. I argue that contending senses, ethnic versus civic, cultural versus political, can be traced back to the formation of the modern concept in the eighteenth century, and that its current ambiguity, or multivocality, is also attributable to that original context. Basic here is the idea that the modern concept arose out of a general crisis, or at least destabilisation, of moral and political authority in that period. I argue that Smith's use of the word 'nation' was fairly conventional for the time, but that without fully intending to, his arguments for 'natural order' laid groundwork for imaginings of self-governing peoples, able to thrive without traditional or unified loci of authority. Smith's theories of emergent social order in the domains of morality and economy were also responses to the weakening of traditional authority, and crucial in the formation of modern concepts of society, which have been inextricably bound up with the idea of the nation-state.